PENGARUH PENGGUNAAN MODEL ADVANCE ORGANIZER BERMEDIA PETA KONSEP TERHADAP KEMAMPUAN MENGANALISIS MATERI SEJARAH SISWA SMA - Imas Devita Sari; Kuswono Kuswono (Swarnadwipa, 2021)
The purpose of this study to determine the effect of the use of advance organizer teaching model bermedia concept maps on the ability to analyze the historical material class X SMA IPS second semester of the country 1 Punggur the Academic Year 2016/2017. This research uses quasi studies (Quasi Experiment), to form Nonequivalent control group design. Samples were selected using cluster random sampling and testing done outside of class X IPS4 sample of classes to 34 students. Validity and Reliability through SPSS 16 results are abnormal and homogeneous. test hypotheses on the equality test two averages using SPSS 16 with the test method K Independent Samples Tests to get the sig 0.006 (<0.05). Having in mind there are further differences in the two different test arithmetic average using SPSS 16 with the test method Two Independent Samples Tests and earn an average yield of 42.97 experimental classroom learning and to control class 29.40. The conclusion of this study is that there is a significant positive influence and advance the use of the learning model of media organizer concept maps on the ability to analyze the historical material class X IPS second semester of SMA Negeri 1 Punggur in academic year 2016/2017.